Calcium Channel Blocker Compared With Angiotensin Receptor Blocker for Patients With Hypertension: A Meta‐Analysis of Randomized Controlled Trials. Issue 11 (7th August 2014) - Wu, Ling; Deng, Song‐Bai; She, Qiang
<x xml:space="preserve">Abstract</x> To explore the clinical effects of a calcium channel blocker compared with an angiotensin II receptor blocker in hypertensive patients, the authors collected data from randomized controlled trials. The pooled outcomes were all‐cause mortality, stroke, myocardial infarction, and heart failure. Eight head‐to‐head trials enrolling 25, 084 patients were included. There was no significant mortality difference in the two arms (relative risk, 0.99; 95% confidence interval, 0.91–1.07). However, calcium channel blockers were more effective in reducing stroke (relative risk, 0.87; 95% confidence interval, 0.76–0.99) and myocardial infarction incidence (relative risk, 0.86; 95% confidence interval, 0.76–0.98). There was no significant difference with heart failure incidence between the two arms but a lower trend in patients with angiotensin II receptor blockers was noted (relative risk, 1.4; 95% confidence interval, 0.99–1.98). The meta‐analysis suggested that initially use of a calcium channel blocker might be superior to an angiotensin II receptor blocker for prevention of stroke and myocardial infarction.